1963
DOI: 10.1021/ic50008a025
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Perchlorates as Bases at Elevated Temperatures: The Depolymerization of Alkali Metal Condensed Phosphates

Abstract: The normal course of pyrolysis of L1CIO4, NaClOt, and KClCh to the metal chlorides is altered to varying degrees to yield effectively the metal oxides in the presence of the corresponding metaphosphates. This behavior reflects an acid displacement reaction which is accompanied by depolymerization of the metaphosphates to simpler anionic species. In this respect the perchlorates are bases relative to the isopolyphosphate anionic acids. The extent of metaphosphate depolymerization is found to be a function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1964
1964
1980
1980

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…LiClOs-Condensed Phosphate Mixtures. It was thought that as in the instance of LiC104 (44), LiClOs might prove effective as a depolymerizing agent for condensed lithium phosphates (e.g., Li4P20-and the polymeric LiPOs) through its decomposition as per Reaction 1 which yields O-2 ions. Total Cl2 evolution and preliminary DTA and TGA studies showed reaction to become measurable at about 250°for the mixtures of Table II which also summarizes the extents of conversion of the LiClOs contents to Li20.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…LiClOs-Condensed Phosphate Mixtures. It was thought that as in the instance of LiC104 (44), LiClOs might prove effective as a depolymerizing agent for condensed lithium phosphates (e.g., Li4P20-and the polymeric LiPOs) through its decomposition as per Reaction 1 which yields O-2 ions. Total Cl2 evolution and preliminary DTA and TGA studies showed reaction to become measurable at about 250°for the mixtures of Table II which also summarizes the extents of conversion of the LiClOs contents to Li20.…”
Section: Resultsmentioning
confidence: 99%
“…Thermoanalytical Techniques. DTA experiments to about 700°were performed in a closed muffle furnace with equipment previously described (35,39,44) in conjunction with calibrated chromel-alumel thermocouples (24 B. and S. gage) and quartz sample tubes (3 The pyrolysis of LiClOs was studied by differential thermal analysis and thermogravimetry at a heating rate of 4°/min., and by isothermal experiments at 339°. The decomposition was shown to follow the sequence: (rapid; ca.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In every case the net reaction with respect to the NOg-ion was 2N03-2N02(g) + 0.5O2(g) + [02i (1) in which [O2-] denotes the effective donation of an oxide ion to a phosphate acid, and does not imply the existence of any appreciable O2-concentration in a nitrate melt.1,2 In all cases studied degradation of any phosphate species did not yield a product simpler than the P2O74-ion, whose double end-group structure apparently represented a stable form in molten NaNOg and nitrates of the heavier alkali metals. However, it was observed that if molten LiNOg was used as the reaction medium, degradation to PO43occurred, indicating a distinct cation effect.1 This is not unexpected in view of work by Markowitz et al, 3 and by other workers cited in extenso in the work of ref 1. The present work constitutes a study of the kinetics of the reaction P2074-+ 2NOg-->-2P043" + 2N02(g) + 0.5O2(g) (2) Li+ with respect to P2074-in excess molten alkali nitrate solvents (55:1 mole ratio of NOg~t o P2074-) as functions of Li+ concentration from 0.6530 to 0.9323 catiop mole fraction, and of temperature over a fairly small range from 610 to 625 K. Lithium content in the molten nitrates was controlled by mixing appropriate quantities of LiNOg and NaNOg.…”
Section: Introductionmentioning
confidence: 87%